Tinjauan Prinsip Non-Retroactive dalam Perjanjian Pengalihan Utang Antara Indonesia dan Belanda - Britha Mahanani Dian Utami (UIN Sunan Kalijaga Yogyakarta, 2023)
This paper discusses about the Dutch debt offering to Indonesia from a non-retroactive perspective. The statement by the Minister of Finance of the Republic of Indonesia reminded of Indonesia's problems, which have been bearing debt even since its proclamation. This debt was inherited from the Netherlands through an agreement in an international agreement called the Konferensi Meja Bundar (KMB). As an international agreement, the KMB must also be guided by the principles in international treaty law. The principle of non-retroactivity is one of the main principles in international law agreements. Even though the principle of non-retroactivity is not absolute and can be deviated, the deviation must be based on two conditions, which are the agreement of the parties and beneficial to the parties or at least does not cause harm to one of the parties. The type of research used in this article is literature and is analytical descriptive with a normative approach. The conclusion of this study shows that the debt offering agreement from the Dutch Government to Indonesia has deviated from the principle of non-retroactivity. Therefore, the agreement to sell debt from the Netherlands to Indonesia has clearly caused losses to the Indonesian Government's finances, besides that there is also an element of coercion in giving approval from the Indonesian Government.Tulisan ini hendak mengkaji kembali tentang perjanjian pengalihan utang Belanda kepada Indonesia yang ditinjau dari prinsip non-retroactive. Pernyataan Menteri Keuangan RI mengingatkan pada persoalan Indonesia yang sudah menghadapi utang bahkan sejak diproklamasikan. Utang ini diwariskan dari Belanda melalui kesepakatan dalam perjanjian internasional bernama Konferensi Meja Bundar (KMB). Sebagai perjanjian internasional, KMB semestinya juga berpedoman pada prinsip-prinsip dalam hukum perjanjian internasional. Asas non-retroactive merupakan salah satu prinsip utama dalam hukum perjanjian internasional. Meskipun asas non-retroactive tidak bersifat mutlak dan dapat disimpangi, namun penyimpangannya harus didasarkan pada dua syarat yakni atas kesepakatan dari para pihak dan menguntungkan bagi para pihak atau setidak-tidaknya tidak menimbulkan kerugian bagi salah satu pihak. Jenis penelitian yang digunakan dalam artikel ini ialah kepustakaan dan bersifat deskriptif analitis dengan pendekatan normatif. Kesimpulan dari penelitian ini menunjukkan bahwa perjanjian pengalihan utang dari Pemerintah Belanda kepada Indonesia telah menyimpangi prinsip non-retroactive. Oleh karena, perjanjian pengalihan utang dari Belanda kepada Indonesia secara jelas telah menimbulkan beban kerugian bagi keuangan Pemerintah Indonesia, selain itu juga terdapat unsur pemaksaan dalam pemberian persetujuan dari Pemerintah Indonesia.